Localization of the F1-ATP Synthase Subunit alpha and its N' and C' Terminal Fragments in Trypanosoma brucei cells - Lehmayer, Leonie (Jihočeská univerzita, 2018)
In this thesis, we explored if the proteolytically excised octapeptide from the Trypanosoma brucei F1-ATP synthase subunit alpha can act as a mitochondrial targeting sequence. Three procyclic 29.13 T. brucei cell lines were generated to express tagged variants of the alpha subunit. We then determined where these heterologous proteins were localized within the parasite. This preliminary data provides insights about where the alpha subunit proteolytic cleavage events occur within the cell.
Localization of the F1-ATP Synthase Subunit alpha and its N' and C' Terminal Fragments in Trypanosoma brucei cells